Probing the atmosphere of HD189733b with the Na i and K i lines. Issue 1 (14th August 2020) - Keles, E; Kitzmann, D; Mallonn, M; Alexoudi, X; Fossati, L; Pino, L; Seidel, J V; Carroll, T A; Steffen, M; Ilyin, I; Poppenhäger, K; Strassmeier, K G; et al.
ABSTRACT: High spectral resolution transmission spectroscopy is a powerful tool to characterize exoplanet atmospheres. Especially for hot Jupiters, this technique is highly relevant, due to their high-altitude absorption, e.g. from resonant sodium (Na i ) and potassium (K i ) lines. We resolve the atmospheric K i absorption on HD189733b with the aim to compare the resolved K i line and previously obtained high-resolution Na i -D line observations with synthetic transmission spectra. The line profiles suggest atmospheric processes leading to a line broadening of the order of ∼10 km/s for the Na i -D lines and only a few km/s for the K i line. The investigation hints that either the atmosphere of HD189733b lacks a significant amount of K i or the alkali lines probe different atmospheric regions with different temperature, which could explain the differences we see in the resolved absorption lines.